Aplikasi Maqasid al-Syari‘ah dalam Pentadbiran Negara: Satu Tinjauan Sejarah Islam - Abdul Rahman, Mohamad Zaidi (Jurnal Fiqh, 2015)
The head of State under Siyasah Syar‘iyyah is authorised to determine the manner in which the Syariah should be governed. His decision, however, must reflect the authority of the state over the public is contingent upon public weal (maslahah). Maqasid Syar‘iyyah on the other hand also promotes/projects on the realisation of benefits (maslahah) and prevention of mischief (mafsadah) in order to make a decision in line with Syariah. Thus, the purpose of this article is to analyse Khulafa’ al-Rasyidin’s decisions as example through selected issues. By using library research, the data is interpreted to identify the elements of maqasid from selected decisions made by the Khulafa’ al-Rasyidin. The result demonstrates that the decisions of Khulafa’ al-Rasyidin are in line with Maqasid al-Syari‘ah even though sometime it seems to conflict with the Prophet’s ruling.